Percutaneous coronary intervention in patients with cancer using bare metal stents compared to drug-eluting stents - Ahmed, Talha; Pacha, Homam Moussa; Addoumieh, Antoine; Koutroumpakis, Efstratios; Song, Juhee; Charitakis, Konstantinos; Boudoulas, Konstantinos Dean; Cilingiroglu, Mehmet; Marmagkiolis, Konstantinos; Grines, Cindy; Iliescu, Cezar A. (Frontiers in Cardiovascular Medicine, 2022)
Background Management of coronary artery disease (CAD) is unique and challenging in cancer patients. However, little is known about the outcomes of using BMS or DES in these patients. This study aimed to compare the outcomes of percutaneous coronary intervention (PCI) in cancer patients who were treated with bare metal stents (BMS) vs. drug-eluting stents (DES). Methods We identified cancer patients who underwent PCI using BMS or DES between 2013 and 2020. Outcomes of interest were overall survival (OS) and the number of revascularizations. The Kaplan–Meier method was used to estimate the survival probability. Multivariate Cox regression models were utilized to compare OS between BMS and DES. Results We included 346 cancer patients who underwent PCI with a median follow-up of 34.1 months (95% CI, 28.4–38.7). Among these, 42 patients were treated with BMS (12.1%) and 304 with DES (87.9%). Age and gender were similar between the BMS and DES groups (p = 0.09 and 0.93, respectively). DES use was more frequent in the white race, while black patients had more BMS (p = 0.03). The use of DES was more common in patients with NSTEMI (p = 0.03). The median survival was 46 months (95% CI, 34–66). There was no significant difference in the number of revascularizations between the BMS and DES groups (p = 0.43). There was no significant difference in OS between the BMS and DES groups in multivariate analysis (p = 0.26). In addition, independent predictors for worse survival included age > 65 years, BMI ≤ 25 g/m2, hemoglobin level ≤ 12 g/dL, and initial presentation with NSTEMI. Conclusions In our study, several revascularizations and survival were similar between cancer patients with CAD treated with BMS and DES. This finding suggests that DES use is not associated with an increased risk for stent thrombosis, and as cancer survival improves, there may be a more significant role for DES.